Field Efficiency and Production Cost of Some Rice Field Tillage Tools in Kecamatan Pangkalan Susu Kabupaten Langkat - Ivan Yolessa Butar-Butar; Lukman Adlin Harahap; Saipul Bahri Daulay (Universitas Sumatera Utara, 2015)
Field eficiency and production cost in this research was to get information on rice field tillage using two-wheels tractor, to calculate effective field capacity and field efficiency, fuel consumption and production cost of tillage using some rice field tillage tools. This research used non-factorial completely random design with treatment of plow types (P) consisted of three types i.e: (P1= Singkal plow, P2= Rotary plow I, P3= Rotary plow II). The parameters were field capacity, fuel consumption, tractor efficiency, and economic analysis.The results showed that the treatments of rice field tillage gave significant effect on effective field capacity, efficiency and fuel consumption. The highest effective field capacity of all the rice field tillage was on field 1 and field 3. The highest tillage efficiency was on field 2. The highest fuel consumption was on field 3. Keywords: plow, rice field, tractor.